2021
DOI: 10.3390/children8050410
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of Feeding Practices and Complications in Patients with Critical Bronchiolitis on Non-Invasive Respiratory Support

Abstract: Limited data exist regarding feeding pediatric patients managed on non-invasive respiratory support (NRS) modes that augment oxygenation and ventilation in the setting of acute respiratory failure. We conducted a retrospective cohort study to explore the safety of feeding patients managed on NRS with acute respiratory failure secondary to bronchiolitis. Children up to two years old with critical bronchiolitis managed on continuous positive airway pressure, bilevel positive airway pressure, or RAM cannula were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 29 publications
(34 reference statements)
1
14
1
Order By: Relevance
“…Previous studies have demonstrated a tendency to provide earlier EN to younger patients, but our study did not show that. 21 However, these groups were not identical. More of the patients in the goal-feed group started their PICU stay requiring NIPPV.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have demonstrated a tendency to provide earlier EN to younger patients, but our study did not show that. 21 However, these groups were not identical. More of the patients in the goal-feed group started their PICU stay requiring NIPPV.…”
Section: Discussionmentioning
confidence: 96%
“…There are clear benefits of EN in the PICU. 12,21 Previous studies demonstrated that EN can be administered to patients on NIV, but safety has not been extensively studied. 17 We found that meeting goal feeds is associated with lower rates of intubation but longer hospital and PICU LOS and duration of NIV.…”
Section: Discussionmentioning
confidence: 99%
“…They found that enteral nutrition was initiated an average of 4 h after initiation of NIPPV and greater energy delivery was achieved when feeding via postpyloric tube compared with gastric tube, and in gastric-fed patients when feeds were continuous compared with intermittent [53]. Aspiration rates reported in these studies were low (<1.5%) [50,51,53]. These studies suggest that enteral nutrition may be feasible for some patients on NIPPV, but future studies should consider identifying selection criteria for the patient cohorts that will benefit the most from this strategy without increasing risk or harm to the patient secondary to delays in initiation or advancement of enteral nutrition and/or aspiration.…”
Section: Enteral Nutritionmentioning
confidence: 96%
“…In children with bronchiolitis, enteral nutrition by nasoenteric tube, breastfeeding or per os, was initiated in 90% of patients within 48 h of admission in one study and within 24 h of admission in 71% in another study [50,51]. Enteral nutrition initiation in children with bronchiolitis requiring NIPPV was associated with improved heart rate and respiratory rate [50,52]. A multicenter European study examined enteral nutrition practices in critically ill children receiving NIPPV due to varied underlying causes for acute respiratory failure [53].…”
Section: Enteral Nutrition and Noninvasive Positivepressure Ventilationmentioning
confidence: 99%
See 1 more Smart Citation